2010
DOI: 10.4061/2010/569154
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using Cranial Electrotherapy Stimulation for Pain in Persons with Parkinson's Disease

Abstract: Objectives. To assess the feasibility of treating musculoskeletal pain in the lower back and/or lower extremities in persons with Parkinson's disease (PD) with cranial electrotherapy stimulation (CES). Design. Randomized, controlled, double-blind trial. Setting. Veterans Affairs Medical Center, Community. Participants. Nineteen persons with PD and pain in the lower back and/or lower extremities. Thirteen provided daily pain rating data. Intervention. Of the thirteen participants who provided daily pain data, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…In clinical trials, reports of pain relief were related to higher changes in NRS and VAS scores after treatment, thus suggesting adequate responsiveness . These scales have been extensively used in PD and some clinimetric data are available . VAS scores were higher in PD patients with pain related to the disease versus those with pain from other sources .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical trials, reports of pain relief were related to higher changes in NRS and VAS scores after treatment, thus suggesting adequate responsiveness . These scales have been extensively used in PD and some clinimetric data are available . VAS scores were higher in PD patients with pain related to the disease versus those with pain from other sources .…”
Section: Resultsmentioning
confidence: 99%
“…Mean, worst, and minimal pain during the month preceding the evaluation were related to EQ‐5D quality‐of‐life score . Both NRS and VAS were responsive to analgesic interventions …”
Section: Resultsmentioning
confidence: 99%
“…Pain severity was reported in 8 trials using the pain subscale of the Visual Analogue Scale (VAS-P) [17,24,26,27,29,30,33,35], in 8 using section 39 of the Parkinson's Disease Questionnaire-39 [16,22,23,31,32,36,37,39], in 4 using the Likert pain scale [18,19,34,38], in 1 using the King Parkinson's Disease Pain Scale [21], in 1 using question 1.9 of the Movement Disorders Society -Unified Parkinson's Disease Rating Scale (MDS-UPDRS Q1.9) [25], in 1 using the McGill Pain Scale [20], and in 1 trial using the Daily Pain Rating Sheet [28] (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The number of trials for each identifiable therapeutic intervention category was 3 for dopaminergic agonists [17][18][19], 2 for cannabinoids and opioids [20,21], 3 for surgical methods [22][23][24], 4 for electrical or Chinese therapies [25][26][27][28], 2 for pardoprunox [29,30], 2 for safinamide [16], 1 for catechol-O-methyltransferase (COMT) inhibitors [31], 1 for multidisciplinary team care [32], and 7 for miscellaneous therapies. Miscellaneous therapies included hydrotherapy [33,34], massage therapy [35], gym training [36], mindfulness therapy [37], vibration therapy [38], and power yoga [39] (Table 1, with further intervention details in Appendix 4).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Finally, Rintala et al (2010) 26 explored the use of cranial electrotherapy stimulation (CES), a non-invasive technique which applies a small amount of current through the head via ear-clip electrodes, to treat pain in PD. A review of the use of CES in chronic pain concluded that CES has been found to be effective in reducing both headache and spinal pain, amongst others.…”
Section: Non-pharmacologic Treatmentmentioning
confidence: 99%